Evaluation of Road Damage on Flexible Pavement Using the Bina Marga Method (Case Study; Leuwiseeng Village Road, Majalengka) - Dicky Alfian; Yusra Aulia Sari (Fakultas Teknik Sipil dan Perencanaan, 2025)
Leuwiseeng village road is one of the connecting roads between villages and is the route passed when heading to the district highway. Roads are the most common transportation infrastructure people use for their daily activities. The condition of this road has several damages, including cracks and holes, as a result of which community activities are disrupted. Therefore, researchers are interested in writing a journal entitled Evaluation of Road Damage on Flexural Pavement Using the Bina Marga Method (Case Study: Leuwiseeng Village Road, Majalengka). This evaluation is used to identify the type and level of damage and provide appropriate repair and maintenance recommendations. Road damage can be caused by various factors, including the quality of materials used, inadequate construction design, and vehicle loads that exceed road capacity. Counting traffic volume: The manual method involves recording the number of vehicles passing through at specific intervals, such as 15 minutes or 1 hour. Routine maintenance involves cleaning the road, checking it, and making minor repairs to the road surface to prevent further damage. Leuwiseeng Village Road is located in Majalengka Regency; the road length studied is 1.2 km. This road is a village road with a road width of 5 meters and a two-way, one-lane road. The data collected are road geometric data, average daily traffic (LHR) data, and road damage types and levels. After the data is processed, the road repair and maintenance are analyzed. The LHR of the Leuwiseeng village road, with a length of 1.2 km, is class 3. The types of damage on this road are alligator cracks, patches, holes, grooves, and wear. Where alligator cracking has the highest percentage of other types of damage, with a value of (14%). The Order of Priority (UP) is 8 with a category> 7, so the handling is carried out with a routine maintenance program every year.